Pakistan - Balochistan Province : Public Financial Management and Accountability Assessment - World Bank (Washington, DC, 2012)
This document reports on a Public Financial Management and Accountability Assessment (PFMAA) for the province of Balochistan. The study was commissioned jointly by the World Bank, the Asian Development Bank (ADB), the UK Department for International Development (DfID), and the European Commission (EC). The Government of Balochistan welcomed the initiative of the World Bank, ADB, DFID and EC in carrying out the PFM assessment. The provincial Finance Department is also working on framing new financial rules in order to streamline utilization of funds while ensuring transparency in financial management.. The PFMAA was conducted against 31 Public Financial Management (PFM) performance measurement indicators in accordance with the Public Expenditure and Financial Accountability (PEFA) framework.